The effect of different milk formulas on dental plaque pH - A. DANCHAIVIJITR, S. NAKORNCHAI, B. THAWEEBOON, P. LEELATAWEEWUD, A. PHONGHANYUDH, C. KIATPRAJAK,& R (Paediatric Dentistry, 2006)
The purposes of this study were (1) to investigate the effect of different milk formulas on dental plaque pH after rinsing with these three categories, type of protein-based formulas (milk-based, soy-based, protein hydrolysate),type of sugar (only lactose, lactose and other sugars, only non-milk extrinsic sugars), and casein ratio (high and low casein), and (2) to observe organic acids formed by different milk formulas.